A comprehensive evaluation of strip performance in multiple blood glucose monitoring systems. (May 2015) - Katz, Laurence B; Macleod, Kirsty; Grady, Mike; Cameron, Hilary; Pfützner, Andreas; Setford, Steven
<x xml:space="preserve">Abstract</x> Accurate self-monitoring of blood glucose is a key component of effective self-management of glycemic control. Accurate self-monitoring of blood glucose results are required for optimal insulin dosing and detection of hypoglycemia. However, blood glucose monitoring systems may be susceptible to error from test strip, user, environmental and pharmacological factors. This report evaluated 5 blood glucose monitoring systems that each use Verio glucose test strips for precision, effect of hematocrit and interferences in laboratory testing, and lay user and system accuracy in clinical testing according to the guidelines in ISO15197:2013(E). Performance of OneTouch® VerioVue™ met or exceeded standards described in ISO15197:2013 for precision, hematocrit performance and interference testing in a laboratory setting. Performance of OneTouch® Verio IQ™, OneTouch® Verio Pro™, OneTouch® Verio™, OneTouch® VerioVue™ and Omni Pod each met or exceeded accuracy standards for user performance and system accuracy in a clinical setting set forth in ISO15197:2013(E).